The Urgency of Implementing Case Method and Team-Based Project Learning Methods in Higher Education - Muhammad Zusanri Batubara; Ika Irayani (Fakultas Tarbiyah dan Keguruan UIN Antasari, 2024)
The Decree of the Minister of Education and Culture of the Republic of Indonesia, Number 3/M/2021 on Key Performance Indicators, has shifted the paradigm of the learning process from teacher-centred to student-centred learning. The case method and team-based project learning methods are the criteria for IKU 7 on classroom learning. This indicator emphasizes collaborative and participatory learning to increase the quality and competitiveness of universities in Indonesia. This research analyses the need to implement case method and team-based project learning methods in higher education. This research was conducted using a qualitative descriptive approach to investigate, describe, and interpret how important the implementation of case and team-based project learning methods is in higher education and the phenomenon of implementing these learning methods in higher education. The research data collection technique is a literature study from books, journal articles, research, and online media. The literature sources are critically analyzed to answer the research objectives and ideas in learning methods. The result of this research is that the case method and team-based project learning methods have advantages in the learning process, including increasing student participation, increasing student motivation, increasing student skills based on graduate morals and ethics, building a pleasant learning atmosphere, improving student soft skills and hard skills, creating students who are more critical and responsible, improving student cognitive aspects, and so on. Case methods and team-based project learning methods are essential to implement in higher education because they are by the MBKM and IKU programs, which emphasize collaborative and participatory learning.